Health Literacy Demand of Printed Lifestyle Patient Information Materials Aimed at People With Chronic Kidney Disease: Are Materials Easy to Understand and Act On and Do They Use Meaningful Visual Aids?. Issue 2 (1st February 2017) - Morony, Suzanne; McCaffery, Kirsten J.; Kirkendall, Suzanne; Jansen, Jesse; Webster, Angela C.
Abstract : People with chronic kidney disease (CKD) need usable information on how to live well and slow disease progression. This information is complex, difficult to communicate, and changes during the course of the disease. We examined lifestyle-related printed CKD patient education materials focusing on actionability and visual aids. From a previous systematic review assessing readability of CKD patient information, we identified materials targeting nutrition, exercise, and self-management. We applied the Suitability Assessment of Materials (SAM) and Patient Education Materials Assessment Tool (PEMAT) to evaluate how easy materials were to understand (understandability) and act on (actionability). We created the 5C image checklist and systematically examined all visual aids for clarity, contribution, contradiction, and caption. Of the 26 materials included, one fifth ( n  = 5, 19%) were rated "not suitable" on SAM and fewer than half ( n  = 11, 42%) were rated "superior." PEMAT mean subdomain scores were suboptimal for actionability (52) and visuals (37). Overall, more than half of all 223 graphics ( n  = 127, 57%) contributed no meaning to the text. Images in three documents (12%) directly contradicted messaging in the text. CKD lifestyle information materials require focused improvements in both actionability of advice given and use of visual aids to support people with CKD to self-manage their condition. The fifth C is culture and is best evaluated by user-testing.